Penerapan Manajemen Partisipatif dalam Optimalisasi Pengelolaan Lembaga Pendidikan - Muhammad, Muhammad (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI SANGATTA Kab. Kutai Timur., 2023)
This research aims to analyze the concepts of participatory management, the application of participatory management, and the optimization of the management of educational institutions through participatory management. The method used is the library research method. (Library Research). Research results show that the concept of participatory management is an approach in the management of educational institutions that involves the active participation of all members of the educational institution in decision-making, planning, implementation, and evaluation processes. As for implementation through joint decision-making, collaborative teams, empowerment of teachers and students, open communication, and the involvement of parents and the community, optimizing the management of educational institutions is done by strengthening the engagement and motivation of all stakeholders, improving the quality of decision-making, accelerating response to change, and creating a dynamic and responsive learning environment. By empowering teachers, students, parents, and administrative staff, participatory management can create opportunities for greater collaboration and more student-oriented decision-making.